SENI TOPENG BUBUR KERTAS SEBAGAI MEDIA KREATIVITAS SISWA KELAS IV SD 3 JEPANG - Alifah, Hasna Nur; Fajrie, Nur; Setiawaty, Rani (Universitas Islam Malang, 2025)
Art education is part of the concept of education related to individual creative expression in conveying aesthetic appreciation experiences, a means of releasing emotions, and developing self-potential. The purpose of this study was to analyze the process and results of students' creativity in making paper mache masks and to determine the average value of students' creativity in creating mask art for students at SD 3 Jepang with 20 fourth-grade students as research subjects. This type of research uses Mixed Methods Sequential Exploratory design. The data collection techniques for this study are observation, interviews, documentation, and questionnaires. Qualitative data analysis used consists of data reduction, data presentation, and drawing conclusions, while quantitative data is in the form of descriptive statistics using SPSS and Microsoft Excel. The results of the study showed that fourth-grade students at SD 3 Jepang have a good level of creativity in carrying out artistic activities of making paper mache masks, both in choosing mask designs and students' creative ways of completing each stage. This is supported by the results of the student creativity questionnaire which is in the high category with an average value of 78.95. This study should be used as a guideline for teachers to implement creativity-based art learning using recycled materials such as paper waste so that students are more sensitive to the surrounding environment. Keywords: Creativity, mask, paper pulp